Acute hypoxia modulate macrophage phenotype accompanied with transcriptome re-programming and metabolic re-modeling - Sun, Binda; Long, Yao; Xu, Gang; Chen, Jian; Wu, Gang; Liu, Bao; Gao, Yuqi (Frontiers in Immunology, 2025)
IntroductionMacrophages, which tend to aggregate in the hypoxic regions of tissues, have a significant impact on disease progression and outcome because of their plastic responsiveness to hypoxia, particularly in the early stages. Understanding macrophages’participation in hypoxia-related disorders requires demonstrating the impact of acute hypoxia on their survival, phenotype, and function.MethodsHere we conducted a systematic evaluation of macrophage responses to hypoxia over 24 and 48 h including cell growth and activity, inflamatory response, macrophage polarization and transcriptional and metabolic changes.ResultsWe found that acute hypoxia suppresses macrophage proliferation and phagocytosis function with a parallel change of transcriptome re-programming and metabolic re-modeling. Although macrophages accumulate transcriptome heterogeneity based on oxygen concentration and culture period, genes involved in hypoxia response, chemotaxis, and glycolytic process were commonly altered during acute hypoxia. Furthermore, the pro-inflammatory response of macrophages was activated during acute hypoxia concomitantly with an enhanced anti-inflammatory regulatory mechanism characterized by increased M2 macrophage population and anti-inflammatory metabolite itaconic acid. Aside from increased glycolysis, the key intermediates in the pentose phosphate pathway significantly increased, such as fructose 1,6-bisphosphate (fold change: 7.8), 6-phosphogluconate (fold change: 6.1), and ribose 5-phosphate (fold change: 3.9), which indicated that the pentose phosphate pathway was an important compensatory metabolic regulation that rules for the response of macrophages to acute hypoxia.DiscussionThese findings highlight that acute hypoxia suppresses macrophage viability and phagocytosis, while acute hypoxia modifies the transcriptome and metabolome in specific inflammatory responses and metabolic pathways to facilitate the adaptation of macrophage in hypoxic conditions.